2013
DOI: 10.1155/2013/604865
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of In Vitro Antioxidant Properties of Methanol and Aqueous Extracts of Parkinsonia aculeata L. Leaves

Abstract: In the present study, methanol and aqueous extracts of Parkinsonia aculeata L. leaves were prepared and analyzed for phytochemical analysis and antioxidant potential in different in vitro assays. Antioxidant activity was studied using DPPH, CUPRAC, reducing power assay, deoxyribose degradation (site and nonsite specific), ferric reducing antioxidant potential (FRAP), ferric thiocyanate (FTC), thiobarbituric acid (TBA), and molybdate ion reduction, respectively. The total phenolic contents of the methanol and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 17 publications
1
39
0
1
Order By: Relevance
“…While the developed antioxidant sensor was characterized with GA, the obtained antioxidant capacity of the tested herbal extracts can be validated by comparing with the antioxidant activity of GA since this approach was done in many studies [47][48][49][50]. Using the standard calibration curve of GA obtained by scanometry technique, the antioxidant capacity of each extract was calculated and expressed as gallic acid equivalent in mg/L (mg/L GAE) as described in our previous work [29].…”
Section: Application Of Antioxidant Sensor On the Plant Extractsmentioning
confidence: 99%
“…While the developed antioxidant sensor was characterized with GA, the obtained antioxidant capacity of the tested herbal extracts can be validated by comparing with the antioxidant activity of GA since this approach was done in many studies [47][48][49][50]. Using the standard calibration curve of GA obtained by scanometry technique, the antioxidant capacity of each extract was calculated and expressed as gallic acid equivalent in mg/L (mg/L GAE) as described in our previous work [29].…”
Section: Application Of Antioxidant Sensor On the Plant Extractsmentioning
confidence: 99%
“…On the basis of chromatogram obtained for all the samples Vig 2013 and, it was concluded that extract/fractions of P. aculeata leaves contain gallic acid, catechin, chlorogenic acid, epicatechin, caffeic acid, umbelliferone, coumaric acid, rutin, ellagic acid, etc. (Table 9).…”
Section: Antimutagenic Activitymentioning
confidence: 99%
“…aculeata L. is a perennial flowering tree from the family Fabaceae. It is widely cultivated in South America, Mexico, South to North Argentina and now introduced and cultivated in South Africa, Uganda and India also (Wagner et al 1999;Pier 2000;Divya et al 2011;Sharma and Vig 2013). Leaves of this plant are prescribed for malaria, fever and as an abortifacient.…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) or free radicals are harmful products or intermediates that may be generated during the processes of biological combustion (Sharma and Vig, 2013;Zaman et al, 2016). The imbalance between oxidants and antioxidants are called oxidative stress, because of the damage in all kinds of biomolecules such as protein, nucleic acid, DNA and RNA (Sharma and Vig, 2013).…”
Section: Introductionmentioning
confidence: 99%